BARROW DECLARATION 2000 on the occasion of the Second Ministerial Meeting of THE ARCTIC COUNCIL - Arctic Council, - (Arctic Council, 2000)
BARROW DECLARATION on the occasion of the Second Ministerial Meeting of THE ARCTIC COUNCIL, October 2000